Tinjauan Yuridis Terhadap Tindak Pidana Kepemilikan Senjata Api Tanpa Hak Oleh Masyarakat Sipil (Putusan Nomor : 79/PID.B/2016/PN.BLG) - Sonya Airini Batubara (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
This study aims to find out how the criminal liability for abuse of firearms is. This study applies normative research method in which the research is conducted based on reading materials such as books, literature and legislation relating to the material to be discussed in this thesis. From the results of the study, it can be concluded that the act of abuse of firearms is that it has become a lifestyle, and causes a sense of self security because of the increasingly widespread circulation of illegal firearms in Indonesia. But the security of our society can actually be disrupted if they are unable to hold back their emotions and are less responsible. Keywords: Abuse, Firearms, Civil Society